Les techniques d’identification inédites mobilisées par Edmond Locard : le graphoscope, le hastoscope et le synchrisiscope - Amos Frappa (Criminocorpus)
During the interwar period, men from Lyon’s police laboratory developed new microscopes in order to more efficiently fight crime. Graphoscope, hastoscope and synchrisiscope evolved at the climax of the structure Edmond Locard created in 1910. Special funding, dynamism of the local industry, interns’ creativity and competition between the French police laboratories are the key elements to explain that sequence of innovations. But were there only enhancements? This question is relevant for each of the innovations. They are only enhanced miscroscopes. Locard’s graphoscope, used for the evaluation of written documents, was part of long term research which had been made in Europe for several decades. The hastoscope and the synchrisicope, designed by the two foreign interns Harry Söderman and William Stirling, are the heirs from the first comparator microscope conceived in Russia at the end of the 19th century. The spread of these instruments out of Lyon’s laboratory allow us to identify them as innovations. Broadcasting these objects needed a offensive commercial strategy through several ways: word of mouth, press diffusion and so on. Graphoscope, hastoscope and synchrisiscope did not have the same use and fate, even inside Lyon’s laboratory. The second was barely used whereas the other two became progressively key instruments in daily operations.